Capital de trabajo y su relación con las NIIF para pymes en las empresas comercializadoras de plásticos - Iler Flores, Diana Steffany (2021)
The present research work named "Working Capital and its relationship with IFRS for SMEs in plastics trading companies" aims to analyze the structure of working capital and the relationship with IFRS for SMEs in the XYZ COMPANY that is in charge of the commercialization of plastics. The objective of this project is to create a methodology of procedures for the adequate administration of working capital and the correct use of IFRS for SMEs in plastics trading companies, presenting the analysis of the qualitative and quantitative variations of the Financial Position Statements, in the years 2017- 2018. As a result, it was possible to determine that working capital is not only a difference between current assets and liabilities, but that its importance lies in carrying out an adequate analysis of the items that make it up, in such a way that allows managers to examine the level of liquidity and profitability, in order to take appropriate measures to maintain financial balance in the entity..........